Peningkatan keterampilan menulis narasi melalui penggunaan model experiential learning peserta didik kelas iv sekolah dasar - Wida Yusiana; St.Y Slamet; Sukarno Sukarno (Didaktika Dwija Indria, 2024)
This study aims to enhance the narrative writing skills of grade IV students at SDN Karangasem IV using the Experiential Learning model, which emphasizes learning through direct experience. The research was conducted using classroom action research (PTK) over two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through writing tests, observations, and interviews. Quantitative data were analyzed using descriptive comparative analysis, while qualitative data were analyzed with the Miles and Huberman interactive model. The results showed a significant improvement in narrative writing skills, particularly in structure, language use, and creativity. The average score increased from 61.05 in the initial condition to 67 in the first cycle and 74.26 in the second cycle. Additionally, the percentage of students meeting the standard of completeness rose from 23% to 46% in the first cycle and 81% in the second. The Experiential Learning model proved effective in improving narrative writing skills.